Tugas Night Auditor di Hotel 88 Embong Kenongo Surabaya - Ajeng Puspa Devi; Diva Nabila Putri; Galang Arjuna; Riris Yuniarsih (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The purpose of this study is to analyze in depth the implementation of night auditor duties at Hotel 88 Embong Kenongo, including job descriptions, audit and data verification processes, roles in guest services, challenges encountered along with handling efforts, and the importance of competence and work readiness in supporting smooth hotel operations. This study employs a qualitative method with a direct observation approach. The findings indicate that the night auditor plays a crucial role in supporting hotel operations, particularly during nighttime. The responsibilities are not limited to auditing and financial data verification but also include guest service and handling various situations that arise. Night auditors are required to have accuracy, communication skills, and strong physical and mental readiness. Various challenges such as limited staff, data errors, and technical issues can be addressed through coordination, repeated checking, and competency improvement. Therefore, the role of the night auditor is key in maintaining the accuracy of reports and the quality of hotel services.